2017 IEEE 23rd International Symposium on on-Line Testing and Robust System Design (IOLTS) 2017
DOI: 10.1109/iolts.2017.8046202
|View full text |Cite
|
Sign up to set email alerts
|

Thermal laser attack and high temperature heating on HfO<inf>2</inf>-based OxRAM cells

Abstract: Abstract-The last 10 years have seen the rise of new NVM technologies as alternative solutions to Flash technology, which is facing downsizing issues. Apart from offering higher performance than the state of the art of Flash, one of their key features is lower power consumption, which makes them even more suitable for the IoT era. But one of the other main concerns regarding IoT is data security, which is yet to be evaluated for emerging NVM. Our previous work aimed at putting under test the integrity of HfO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…However, no faults were injected by the different laser tests, although a catastrophic failure was eventually caused when continuous test was applied, destroying the resistive switching behavior of the device. These results are in line with the ones reported in [24], but are different from the ones in [25,26], where, according to the authors, the devices were disturbed in HRS, passing to the LRS after the laser pulse due to a heating effect. The results of the present work can be useful for a better understanding of RRAM devices under the influence of laser attacks.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, no faults were injected by the different laser tests, although a catastrophic failure was eventually caused when continuous test was applied, destroying the resistive switching behavior of the device. These results are in line with the ones reported in [24], but are different from the ones in [25,26], where, according to the authors, the devices were disturbed in HRS, passing to the LRS after the laser pulse due to a heating effect. The results of the present work can be useful for a better understanding of RRAM devices under the influence of laser attacks.…”
Section: Discussionsupporting
confidence: 82%
“…This behavior was attributed to the charge collection on the corresponding access transistor of the cell, since the RRAMs were reported to be insensitive in a standalone configuration. Another experiment was carried out in single RRAMs [25,26] where the devices were disturbed by laser exposition, performing also transitions from HRS to LRS. In this case, this behavior was justified by temperature increase brought by laser heating.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent works have addressed possible security issues of such emerging NVMs. For instance, the authors of [9] and [10] have studied the effect of active attacks on the Oxide-based Resistive Random Access Memory (OxRRAM). These works showed that OxRRAM cells could be easily attacked by laser injections.…”
Section: B Security Issuementioning
confidence: 99%
“…Recent works evaluated the thermal effect impact on emerging non-volatile memory induced by a laser irradiation, on the OxRAM technology [12] and on the STT-MRAM memory [13]. This thermal effect is mostly induced by frontside laser injections.…”
Section: ) Thermal Effectmentioning
confidence: 99%
“…Thus, their hardening and robustness is essential. Recently, it has been demonstrated that front-side laser injection may also generate faults on the Back-End of Line (BEoL) of emerging non-volatile memories such as Resistive Random Access Memory (RRAM) [12] or Spin Transfer Torque Magnetic Random Access Memory (STT-MRAM) [13]. Thus, it is now mandatory to also detect laser attacks targeting the STT-MRAM.…”
Section: Introductionmentioning
confidence: 99%